Association of obesity susceptibility gene variants with metabolic syndrome and related traits in 1,443 Czech adolescents - Dušátková, L; Zamrazilová, H; Sedláčková, B; Včelák, J; Hlavatý, P; Aldhoon Hainerová, I; Korenková, V; Bradnová, O; Bendlová, B; Kunešová, M; Hainer, V (Folia biologica, 2013)
Genome-wide association studies have revealed several gene variants associated with obesity; however, only a few studies have further investigated their association with metabolic syndrome. We performed a study of eleven variants in/near genes TMEM18, SH2B1, KCTD15, PCSK1, BDNF, SEC16B, MC4R, and FTO in Czech adolescents and analysed their association with obesity, metabolic syndrome and related traits. Genotyping was performed in 1,443 adolescents aged 13.0-17.9 years. Anthropometric parameters, biochemical parameters and blood pressure were assessed. Metabolic syndrome was defined according to the International Diabetes Federation. The FTO rs9939609 variant was associated with overweight/obesity (OR 1.40, 95% CI 1.21-1.63, P < 0.001). The minor allele of TMEM18 rs7561317 was related to underweight (OR 1.78, 95% CI 1.14-2.79, P = 0.015). BDNF rs925946 and MC4R rs17782313 were associated with metabolic syndrome (OR 1.53, 95% CI 1.14-2.04, P = 0.005; 1.51, 95% CI 1.12-2.04, P = 0.009). The PCSK1 rs6235 variant was negatively related to increased blood glucose (OR 0.69, 95% CI 0.49-0.97, P = 0.040). In conclusion, the FTO variant was associated with overweight/obesity in Czech adolescents. Moreover, MC4R and BDNF variants increased the risk of metabolic syndrome, probably through their effect on abdominal obesity. The PCSK1 variant may have a protective role in the development of type 2 diabetes.
Keywords: hubenost; Genetic Predisposition to Disease; C-Peptide; lipidy; celogenomová asociační studie; genotyp; Obesity; krevní glukóza; adipozita; Metabolic Syndrome; Genotype; mladiství; Česká republika; Cohort Studies; inzulin; mužské pohlaví; Insulin; Overweight; Czech Republic; kohortové studie; Adiposity; Lipids; Blood Glucose; ženské pohlaví; Anthropometry; metabolický syndrom; Humans; frekvence genu; antropometrie; obezita; nadváha; C-peptid; Gene Frequency; Genome-Wide Association Study; genetická predispozice k nemoci; Female; Adolescent; Thinness; lidé; Male